Toxic dispossession and environmental violence in Latin America - Diego Andrés Lugo-Vivas; Irene Vélez-Torres (Journal of Political Ecology, 2024)
The emission of pollutants from industrial, extractive (mining and hydrocarbons), and corporate agricultural activities exacerbates environmental degradation, endangering sustainable living conditions for humans and more-than-humans. Growing concerns revolve around the chronic and acute exposure to hazardous substances, often leading to compounded, cumulative, and irreversible consequences in socio-ecosystems and human health. Yet, resorting to the anthropogenic origins of socio-ecological damages resulting from widespread contamination does not fully elucidate the intricate biopolitical and geopolitical dynamics underlying the intoxication of cuerpxs-territorixs [bodies-territories]. This Special Section comprises five articles that leverage existing scholarship in political ecology and related fields to critically analyze the political ecologies of toxic dispossession, socio-ecological degradation, and forced environmental changes driven by extractivism. Drawing on the analysis of different cases from Latin America, the authors elucidate how environmental violence, toxic dispossession, and environmental suffering root in the extractive and predatory models rooted in colonial legacies, unresolved racial, ethnic and gendered inequalities, and the expansion of contemporary capitalism in the Global South.